The twins stories : participant coding in Yagua narrative - Payne, Thomas Edward, 1951- (Berkeley (Calif.) : University of California press, 1993)
This work is a quantitative discourse study of referential devices in Yagua, a relatively unstudied language of the Amazon basin. Of particular interest are folktales in which the major participants are matched pairs, and which involve extensive use of direct speech. A major finding is that the indices of "Referential Distance" and "Persistence" quantify distinct functional domains.
Includes bibliographical references (p. 215-222).
Keywords: Yagua Indians -- Folklore; Yagua language -- Discourse analysis; Yagua language -- Grammar